On the C++ Object Programming for Time Series, in the Linux framework - George Daniel Mateescu (Romanian Academy, National Institute for Economic Research, 2013)
We study the implementation of time series trough C++ classes, using the fundamentals of C++ programming language, in the Linux framework. Such an implementation may be useful in time series modelling.
Keywords: C23; 330; Object Programming; Time Series